2020
DOI: 10.1073/pnas.1918578117
|View full text |Cite
|
Sign up to set email alerts
|

Removing a single neuron in a vertebrate brain forever abolishes an essential behavior

Abstract: The giant Mauthner (M) cell is the largest neuron known in the vertebrate brain. It has enabled major breakthroughs in neuroscience but its ultimate function remains surprisingly unclear: An actual survival value of M cell-mediated escapes has never been supported experimentally and ablating the cell repeatedly failed to eliminate all rapid escapes, suggesting that escapes can equally well be driven by smaller neurons. Here we applied techniques to simultaneously measure escape performance and the state of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 55 publications
2
64
0
Order By: Relevance
“…Since this range composes a significant proportion of the experimentally observed range of times remaining at escape, there is a clear functional benefit of recruiting the Mauthner neuron in this predatory context. This is further supported by recent experimental evidence which shows that larval zebrafish are far less likely to survive dragonfly nymph strikes after Mauthner cell ablation [16].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Since this range composes a significant proportion of the experimentally observed range of times remaining at escape, there is a clear functional benefit of recruiting the Mauthner neuron in this predatory context. This is further supported by recent experimental evidence which shows that larval zebrafish are far less likely to survive dragonfly nymph strikes after Mauthner cell ablation [16].…”
Section: Discussionsupporting
confidence: 73%
“…Fish motor volumes representing Mauthner active and silent responses ( Figure 7D) were generated by pseudo-randomly sampling different uniform distributions of initial bend velocities. The range of bend velocities for Mauthner silent motor volumes was 10 ± 5 deg/sec and for Mauthner active motor volumes it was 18 ± 5 deg/sec based on prior studies that investigated bend velocities of free swimming larval zebrafish before and after Mauthner ablation [41,42,16]. The ranges were also constructed to have some overlap since studies have found that Mauthner active and silent responses can on occasion produce similar kinematics [43,44].…”
Section: Computational Motor Volume Of Larval Zebrafishmentioning
confidence: 99%
See 1 more Smart Citation
“…Zebrafish is an excellent vertebrate model to interrogate gene function in the establishment of neural circuits in vivo and associated behaviours (Kalueff et al, 2013;Mcarthur et al, 2020). One of the most studied neural circuits is the Mauthner cell mediated acoustic startle circuit (Swain et al, 1993;Jontes et al, 2000;Korn and Faber, 2005;Burgess et al, 2009;Sillar, 2009;Issa et al, 2011;Kinkhabwala et al, 2011;Hale et al, 2016;Liu and Hale, 2017;Hecker et al, 2020). Acoustic and tactile stimuli from the environment are processed by the M-cells aided by regulatory excitatory and inhibitory interneuron module and relayed to the motor neurons downstream (Korn and Faber, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Issues range from access to consistent, high-quality human autopsy materials of comparable age, sex, and race or sequencing technologies and bioinformatics not optimized for mosaicism to biological impediments like nonclonal genomic alterations affecting just a single postmitotic cell, obfuscated by a sea of normal cells. For example, the brain shows functional uniqueness of very small populations of cells, such as neurons responsive to input from a particular point in visual space (30,31) or even the proposed single "grandmother" cell that responds to a complex assembly of visual features such as those comprising a specific face (32), yet most sequencing techniques only allow detection of de novo somatic mutations present in .1-10% of cells (33). In the human brain, this represents a background of tens of billions (10 10 ) of unaffected cells preventing mutation detection even for some clonally expanded mutations, let alone isolated single-cell changes that would require sequencing sensitivity and specificity many logs beyond current technologies.…”
mentioning
confidence: 99%